Commercial Production and Chemical/Physical Characterization of Natural and Nutritious Coconut Sap Food Products (Cocosap Juice and Cocosap Concentrate) at Tawan-tawan, Baguio District, Davao City, Southern Mindanao, Philippines - Millicent I. Secretaria (CORD, 2008)
The processing of natural and nutritious coconut sap juice and coconut sap concentrate for commercial production was conducted by the members of the Samahang Magniniyugan ng Tawan-tawan (SMT) at Barangay Tawan-tawan, Baguio District, Davao City, Southern Mindanao, Philippines from February to May, 2007. The processing of coconut sap juice and concentrate involves simple, easy to follow procedures and few equipment are required.